2014
DOI: 10.1007/s00894-014-2067-1
|View full text |Cite
|
Sign up to set email alerts
|

Parallel implementation of 3D protein structure similarity searches using a GPU and the CUDA

Abstract: Searching for similar 3D protein structures is one of the primary processes employed in the field of structural bioinformatics. However, the computational complexity of this process means that it is constantly necessary to search for new methods that can perform such a process faster and more efficiently. Finding molecular substructures that complex protein structures have in common is still a challenging task, especially when entire databases containing tens or even hundreds of thousands of protein structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…Hwang et al implemented a GPU version of DUST in which they performed probability computations to accelerate the performance of the initial version of DUST . To identify the structural similarity in exponentially growing protein dataset, Mrozek et al proposed a GPU‐based CASSERT technique named GPU‐CASSERT . The Bloom filter–based similarity search is used for privacy preserving record linkage used in many real‐world health care systems by different countries such as Australia, Brazil, Germany, and Switzerland.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Hwang et al implemented a GPU version of DUST in which they performed probability computations to accelerate the performance of the initial version of DUST . To identify the structural similarity in exponentially growing protein dataset, Mrozek et al proposed a GPU‐based CASSERT technique named GPU‐CASSERT . The Bloom filter–based similarity search is used for privacy preserving record linkage used in many real‐world health care systems by different countries such as Australia, Brazil, Germany, and Switzerland.…”
Section: Related Workmentioning
confidence: 99%
“…For efficiency, GPU uses a single program called kernel to process multiple data items in parallel. The GPU‐based implementations do not reduce the program complexity, but, because of massive parallel processing, it reduces the overall processing time . In such programming models, all datasets must be independent of each other.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A single‐thread A* search algorithm implemented on CUDA‐enabled NVIDIA Tesla K20c GPU yielded 45‐fold acceleration compared to the traditional C implementation on Intel Xeon E5‐1620 CPU . A 3D protein structure similarity searching algorithm implemented on GTX 560Ti GPU has shown a 180‐fold increase in speed compared to a single‐thread implementation on Intel Xeon E5620 . Dang et al reported speed up of about one order of magnitude for CUDA‐based implementation of a clustering algorithm on GeForce Titan GPU compared to a multi‐threaded CPU implementation on a Core‐i7 2700.…”
Section: Introductionmentioning
confidence: 99%
“…GPGPU (General-Purpose computing on Graphics Processing Unit) is a typical instance. Example implementations: two-list algorithm for the subset-sum problem [9] or protein structure similarity search engine [10] illustrate the approach-parallel algorithms execution on GPU requires adjusting to the specific architecture.…”
Section: A Parallel Algorithms Testingmentioning
confidence: 99%